Padronização do teste de tetrazólio para avaliação da viabilidade de sementes de três espécies florestais - Fogaça, Cristiane Alves [UNESP] (2003)
This work had objective to verify the aplicability of tetrazolium test in the evaluation of viability of Astronium graveolens, Jacaranda cuspidifolia and Parapiptadenia rigida seeds. Initialy, were realized morphological study of seeds and seedlings of these species. For the standardization of tetrazolium test were evaluated different conditions of prepare and coloration of the seeds, analyzing the aspects of the tissues and the intensity and uniformity of coloration. Were elaborated viability class diagrams for each specie. The efficiency of tetrazolium test were evaluated comparing the results of that with of the germination test. Concluded that different conditions of tetrazolium test were efficient in the obtaintion of satisfactory coloration, permitting to differentiation of the tissues, showing been adapted for evaluation of viability of Astronium graveolens, Jacaranda cuspidifolia and Parapiptadenia rigida seeds, when compared with the germination test. The choice from the prepare and of the coloration conditions, stayed to criterion of the analyst of seeds, in fuction of the facility operational and urgency of the results.